TINJAUAN HUKUM POSITIF DAN EKONOMI SYARIAH TERHADAP JUAL BELI TANAH TANPA AKTA TANAH DI DESA SANA LAOK KEC. WARU KAB. PAMEKASAN - Moh Fad Lillah; Suhartono Suhartono (Universitas Muhammadiyah Surabaya, 2023)
Certificate of land rights as a strong means of proof against land registration. The guarantee of legal certainty to holders of land rights is accommodated in Law Number 5 of 1960 concerning Agrarian Principles and further regulated in Government Regulation Number 24 of 1997 concerning Land Registration. With the existence of a land certificate, it becomes strong in its ownership and becomes proof if asked to have a dispute over the land This study aims to explore the practice of buying and selling land without a land certificate and interpreting the practice of buying and selling land without a deed with a review of Islamic Economic Law. The type of research conducted by researchers is a type of field research using a phenomenological approach, data collection techniques are obtained by seeking answers about the meaning of a phenomenon while data analysis techniques are obtained by completely describing the phenomena experienced by the research. subject. The results of this study can be concluded that according to Islamic law buying and selling land without land certificates in Sana Laok Village is said to be valid and in accordance with Islamic law even though there is no evidence (certificate) because no one feels a loss. In accordance with the Qur'an (Q.S. Al-Baqarah [2]: 275), which explains that Allah has justified buying and selling and forbidding usury, and the Qur'an (Q.S. An Nisa [4]: 29), and there is no coercion and both sellers and buyers love each other suma or willingly even though there is no evidence (deed) and are honest with each other, because honest people will be in the hereafter with the prophets, martyrs and shiddiqin.Keywords: Positive Law Review, Islamic Economic,Buying And Selling land